The protective role of vitamin C against linezolid-induced hepato-renal toxicity in a rat model - Azzam, Shaimaa M.; Anwar, Hend Mohamed; Abd El-Slam, Ahmed H.; Diab, Marwa S. M.; Ibrahim, Halima Mohamed; Yousef, Abdalrahman Mohammed; Sabry, Fatma Mahmoud; Darwish, Ibrahim A.; Kaliyamoorthy, Kalidasan; Salem, Gad Elsayed Mohamed; Elsanhory, Heba M. A. (Frontiers in Pharmacology, 2025)
This study investigated the protective effects of vitamin C against linezolid-induced hepatotoxicity and nephrotoxicity in rats using biochemical, histopathological, and immunohistochemical methods. Twenty-four rats were divided into four groups: control, linezolid (100 mg/kg/day), vitamin C (100 mg/kg/day), and a combination of vitamin C and linezolid for 14 days. Linezolid treatment resulted in lactic acidosis, increased serum levels of AST, ALT, urea, creatinine, and albumin, and oxidative stress characterized by decreased catalase activity and reduced glutathione (GSH) associated with increased nitric oxide (NO) malondialdehyde (MDA). Pro-inflammatory markers (IL-1β, TNF-α) and renal CD68 expression also increased. Linezolid disrupted autophagy (reduced Beclin-1 levels) and induced apoptosis through hyperactivation of Wingless/integrated (Wnt) signaling (increased Wnt 7a and Wnt 10a expression). Treatment with vitamin C alleviated linezolid side effects by reducing AST, ALT, urea, creatinine, lactic acid, IL-1β, TNF-α, NO, MDA, and Wnt signaling markers while increasing albumin, catalase, GSH, and Beclin-1 levels. Histopathological and immunohistochemical analyses confirmed significant protection of liver and kidney tissues in rats co-administered vitamin C with linezolid. These results suggest that vitamin C can effectively alleviate hepatotoxicity and nephrotoxicity caused by linezolid.